Larger First-Trimester Placental Volumetric Parameters Are Associated With Lower Pressure and More Flow-Mediated Vasodilation of the Fetoplacental Vasculature After Delivery - Hitzerd, Emilie; Reijnders, Igna F.; Mulders, Annemarie G. M. G. J.; Koning, Anton H. J.; Reiss, Irwin K. M.; Danser, A. H. Jan; Steegers-Theunissen, Régine P. M.; Simons, Sinno H. P.; Koster, Maria P. H. (Frontiers in Physiology, 2020)
Objective: To explore the correlation between in-vivo placental volumetric parameters in the first trimester of pregnancy and ex-vivo parameters of fetoplacental vascular function after delivery. Methods: In ten singleton physiological pregnancies, placental volume (PV) and uteroplacental vascular volume (uPVV) were measured offline in three-dimensional ultrasound volumes at 7, 9 and 11 weeks gestational age (GA) using Virtual Organ AnaLysis and Virtual Reality. Directly postpartum, term placentas were ex-vivo dually perfused and pressure in the fetoplacental vasculature was measured to calculate baseline pressure (pressure after a washout period), pressure increase (pressure after a stepwise fetal flow rate increase of 1 mL/min up to 6 mL/min) and flow-mediated vasodilation (FMVD; reduction in inflow hydrostatic pressure on the fetal side at 6mL/min flow rate). Correlations between in-vivo and ex-vivo parameters were assessed by Spearman’s correlation coefficients (R). Results: Throughout the first trimester, PV was negatively correlated with pressure increase (Rgrowth=-0.84) and, at 11 weeks GA, also positively correlated with FMVD (R=0.89). At 7 weeks GA, uPVV and uPVV/PV ratio were negatively correlated with pressure increase (R=-0.58 and R=-0.81, respectively) and positively correlated with FMVD (R=0.62 and R=0.90, respectively). Discussion: Mainly in the early first trimester, larger placental volumetric parameters are associated with lower pressure and more FMVD in the fetoplacental vasculature after delivery. This may suggest that larger and/or more vascularized placentas in early pregnancy have better adaptive mechanisms and possibly lead to better pregnancy outcomes.